Association between col1a2 Polymorphism and the Occurrence of Pelvic Organ Prolapse in Brazilian Women - Rosa, Josyandra Paula de Freitas; Haddad, Raphael Federicci; Maeda, Fabiana Garcia Reis; Souto, Ricardo Peres; Fernandes, Cesar Eduardo; Oliveira, Emerson de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To evaluate the rs42524 polymorphism of the procollagen type I alpha (α) 2 (COL1A2) gene as a factor related to the development of pelvic organ prolapse (POP) in Brazilian women.Methods The present study involved 112 women with POP stages III and IV (case group) and 180 women with POP stages zero and I (control group). Other clinical data were obtained by interviewing the patients about their medical history, and blood was also collected from the volunteers for the extraction of genomic DNA. The promoter region of the COL1A2 gene containing the rs42524 polymorphism was amplified, and the discrimination between the G and C variants was performed by digestion of the polymerase chain reaction (PCR) products with the MspA1I enzyme followed by agarose gel electrophoresis analysis.Results A total of 292 women were analyzed. In the case group, 71 had the G/G genotype, 33 had the G/C genotype, and 7 had the C/C genotype. In turn, the ratio in the control group was 117 G/G, 51 G/C, and 11 C/C. There were no significant differences between the groups.Conclusion Our data did not show an association between the COL1A2 polymorphism and the occurrence of POP.
Keywords: procollagen type I alpha (α) 2 gene; polymorphism; pelvic organ prolapse